Right Ventricular Cardiomyopathies: A Multidisciplinary Approach to Diagnosis. (19th September 2014) - Limongelli, Giuseppe; Rea, Alessandra; Masarone, Daniele; Francalanci, M. Paola; Anastasakis, Aris; Calabro', Raffaele; Maria Giovanna, Russo; Bossone, Eduardo; Elliott, Perry Mark; Pacileo, Giuseppe
Abstract : The physiological importance of the right ventricle (RV) has been underestimated over the past years. Finally in the early 1950s through the 1970s, cardiac surgeons recognized the importance of RV function. Since then, the importance of RV function has been recognized in many acquired cardiac heart disease. RV can be mainly or together with left ventricle (LV) affected by inherited or acquired cardiomyopathy. In fact, RV morphological and functional remodeling occurs more common during cardiomyopathies than in ischemic cardiomyopathies and more closely parallels LV dysfunction. Moreover, there are some cardiomyopathy subtypes showing a predominant or exclusive involvement of the RV, and they are probably less known by cardiologists. The clinical approach to right ventricular cardiomyopathies is often challenging. Imaging is the first step to raise the suspicion and to guide the diagnostic process. In the differential diagnosis, cardiologists should consider athlete's heart, congenital heart diseases, multisystemic disorders, and inherited arrhythmias. However, a multiparametric and multidisciplinary approach, involving cardiologists, experts in imaging, geneticists, and pathologists with a specific expertise in these heart muscle disorders is required.